(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Whether it was British or Indian reformers or politicians, they all viewed the position and status of women of India as one of the indices in which measure the area of modernization and traditionalism of action. The light was shed on women’s political issues and main point of the argument, controversy, accusations. There only two sides that opposed this trend they were British and the Indians, they both were holding conservative opinion. In order to judge the position of women, the British scholars, missionaries and bureaucrats had tried the European standards and values.